Avaliação radiográfica da aplicação do polímero de mamona em falhas ósseas induzidas em equinos - Dornbusch, Peterson Triches; de Araujo, Ivo Guilherme Ribeiro; Tasquetti, Ubirajara Yobe; Pimpão, Claudia Turra; Prado, Antonia Maria Binder; Hussni, Carlos Alberto [UNESP] (My University, 2010)
It was evaluated the radiographs alteration of the castor oil bean polymer applied for the filing of induced bone fault in horses. Five animals were evaluated, subjected to a local anesthesia and sedation, proceeding to a surgical induction of a hole in the radio bone, in both members with three centimeters depth perforations. It was used a drill of eight millimeters of diameter. The right member served as a control, without filling induced holes. The holes in left radio were filled with the commercial polymer derived from the castor oil bean. We evaluated the localized swelling and radiological aspects as: the establishment of scores for bone filling, sclerosis and a morphometric analysis of the sclerosis area, in 15, 45, 90 and 180 days of lesion evolution. There was more swelling in local members whose injuries were filled with polymer from castor oil bean. By comparison, the radiographic examination showed better bone filling in the gaps of members control. We concluded that the completion of castor oil bean polymer in bone holes induced in radio of horses, delayed the bone healing, in the radiographic evaluation.
Radiografhic evaluation of castor oil bean polymeric aplication in equine induced bone flaws
Keywords: Bone cement; Equine; Polymers; Ricinus communis; Animalia; Equidae